Bioresorbable polymer and durable polymer metallic stents in coronary artery disease: a meta-analysis. (4th May 2021) - Mir, Tanveer; Shanah, Layla; Ahmad, Usman; Sattar, Yasar; Chokshi, Bhavin; Aggarwal, Ankita; Prakash, Preeya; Attique, Hassan Bin; Changal, Khalid Hamid; Kumar, Kartik; Alraies, Chadi; Qureshi, Waqas T; et al.
ABSTRACT: Background: Literature on bioresorbable-polymer-stents (BPS) and second-generation durable-polymer-stents (DPS) in percutaneous coronary intervention (PCI) for all comer CAD is conflicting. Methods: Randomized controlled studies comparing PCI among BPS and second-generation DPS were identified up until May-2020 from online databases.  Primary outcomes included are all-cause myocardial infarction (MI), cardiac-death, target-vessel-revascularization (TVR), target-vessel MI (TVMI), and stent-thrombosis (ST). Random effect method of risk ratio and confidence interval of 95% was used. Results: 25 prospective randomized controlled trials with 31, 822 patients (BPS n = 17, 065 and DPS n = 14, 757) were included in the study. Follow–up ranged between a minimum of 6 months to more than 5 years. Cardiac death (RR 1.02, 95% CI 0.89–1.45, p = 0.16) was comparable in BPS and second-generation DPS. Risk of all-cause MI was similar between BPS and DPS (RR 0.97, 95% CI 0.84–1.11, p = 0.73). TVMI (RR 0.88, 95% CI 0.69–1.11, p = 0.33) and ST rates were also comparable in BPS and DPS groups (RR 1.06, 95% CI 0.80–1.40, p = 1.00). Overall TVR had comparable outcomes between BPS and DPS (RR 0.95, 95% CI 0.79–1.14, p < 0.001); however, higher TVR was seen among BPS group at follow-up of ≥5 years (RR 1.39, 95% CI 1.12-1.14, p = 0.02). Bias was low and heterogeneity was moderate. Conclusion: Patients undergoing PCI treated with BPS had comparable outcomes in terms of cardiac death, TVR, ST, TVMI, and all-cause MI to patients treated with second-generation DPS; however, BPS had higher rates of TVR for follow-up of ≥5-years.